INDEKS KEPUASAN INFRASTRUKTUR KABUPATEN INDRAGIRI HILIR TAHUN 2022 - Alfassa, Achmad Isya; Alfa, Akbar; Susanto, Bayu Fajar; Rosmiar, Rosmiar (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2023)
Based on the Minister of State Apparatus Empowerment and Bureaucratic Reform Regulation Number 14 of 2017 concerning Guidelines for Preparing Community Satisfaction Surveys for Public Service Organizing Units and Regional Medium Term Development Plan Documents (RPJMD) for Indragiri Hilir Regency for 2018-2023 which have been stipulated in Regional Regulation Number 10 In 2019, placing infrastructure and a sense of security as a development mission in an effort to achieve the vision of Indragiri Hilir Regency "INHIL PROPERTY THAT IS MORE ADVANCED, WONDERFUL AND Dignified" in 2023. The Infrastructure Service Satisfaction Index (IKLI) is a measure used to measure the level of user satisfaction with infrastructure services that are available. This index is usually calculated by measuring the level of dissatisfaction or satisfaction felt by users with the services available. Users are surveyed to identify their level of satisfaction with the available infrastructure services. In general, the infrastructure service satisfaction index value for 2022 is 65.02. Based on the table of Perception Value, Interval Value, Conversion Interval Value, Service Quality, and Service Unit Performance in Permenpan-RB 14/2017, it can be seen that the sense of security index is MEDIUM for 2022. Berdasarkan dengan Peraturan Menteri Pendayagunaan Aparatur Negara dan Reformasi Birokrasi Nomor 14 Tahun 2017 Tentang Pedoman Penyusunan Survei Kepuasan Masyarakat Unit Penyelenggara Pelayanan Publik dan Dokumen Rencana Pembangunan Jangka Menengah Daerah (RPJMD) Kabupaten Indragiri Hilir Tahun 2018-2023 yang telah di tetapkan dalam Peraturan Daerah Nomor 10 Tahun 2019 menempatkan Infrastruktur dan rasa aman sebagai Misi Pembangunan dalam upaya mencapai Visi Kabupaten Indragiri Hilir “KEJAYAAN INHIL YANG SEMAKIN MAJU, BERMARWAH DAN BERMARTABAT” tahun 2023 Indeks Kepuasan Layanan Infrastruktur (IKLI) adalah suatu ukuran yang digunakan untuk mengukur tingkat kepuasan pengguna atas layanan infrastruktur yang tersedia. Indeks ini biasanya dihitung dengan mengukur tingkat ketidakpuasan atau kepuasan yang dirasakan oleh pengguna terhadap layanan yang tersedia. Pengguna disurvei untuk mengidentifikasi tingkat kepuasan mereka dengan layanan infrastruktur yang tersedia. Secara umum, nilai Indeks kepuasan layanan infrastruktur tahun 2022 adalah 65.02. Berdasarkan table Nilai Persepsi, Nilai Interval, Nilai Interval Konversi, Mutu Pelayanan dan Kinerja Unit Pelayanan pada Permenpan-RB 14/2017, dapat diketahui bahwa Indeks rasa aman adalah SEDANG untuk tahun 2022.